Disiplin Tubuh Pesilat Persaudaraan Setia Hati Terate: Formasi Pembentukan Subjektivitas - Ilma Megasari; Hery Prasetyo (DIMENSI - Jurnal Sosiologi, 2017)
Persaudaraan Setia Hati Terate (PSHT) in applying the disciplinary practices of the body is inseparable from the roots to the Javanese tradition. The cultural root, become a ritual that must be passed by the students (siswa) to become citizens (warga) and they applied to any cultural spaces that are part of existence PSHT. In Suro, there is culmination of the ritual in PSHT that are part of the discipline include: body workout; mental; spiritual, and the consequences are intended to form the subjectivity of citizens. This research focuses on how the disciplinary bodies of PSHT can be formed in Jember cultural setting? This issue has become urgent in putting kejawen tradition that is part of the way PSHT articulating identity. The perspective used in this study is Foucault’s point of view, which focuses on power relations are structured through the practice of discourse. This study uses a discursive approach that put the subject on the space power that emerges from units of statements and events that organize how morality and knowledge driven.